Single-Phase Generalized Switched-Capacitor Multilevel Inverter Using Reduced Number of Power Semiconductor Components with Voltage Boosting Ability - Neti, Sukhdev Singh; Anand, Vishal; Singh, Varsha (Arabian journal for science and engineering (2011), 2022)
This research paper proposes a new switched-capacitor topology for the multilevel inverter. The structure has two isolated DC power supplies and a capacitor. Since the topology uses only one capacitor, it eliminates the problem of voltage balancing across the capacitors. This structure produces 13-level output voltage across the load terminals. The structure can be extended using derived generalized equations. A comparative analysis shows the number of components used with respect to other 13-level inverters existing in the literature. The power loss and efficiency of the topology are evaluated and experimentally verified. Moreover, the output voltage and current waveform for the topology is tested for pure resistive, inductive load, the impact of change in modulation index, and impact of the sudden change in load and is simulated and later verified experimentally using a dSPACE-1104 real-time controller.